Vidas Medicalizadas: por uma Genealogia das Resistências à Farmacologização - Galindo, Dolores (2014)
This paper aims at setting into discussion, in a theoretical essay format, the topic of medicalization and pharmaceuticalization of existence. It discusses the multiplicity of events that support medicalization and the field of struggles in which such situations take place and are materialized into a subjectivizing pharmaceuticalization device. Thus, some features of Rodrigo Souza Leão's work are retrieved which argue on the dimensions of current subjectivizing manners hatched out in the pharmaceutical industry economic policy and that set freedom practices. One concludes, by the end of the paper, that diffusion of medicalization and pharmaceuticalization of life is a widespread practice and, therefore, resistances targeting them need to be increasingly expanded and articulated aiming at producing effects in current society to open gaps that reverberate non medicalizing practices in a tension field of forces. We propose that genealogy of resistances to medicalization of existences should be articulated with the composition of non-conformist files capable of evidencing that, in spite of the pharmaceuticalization power in setting up our subjectifications, freedom practices continue to be plotted in their interstices.